Exercise ameliorates high fat diet induced cardiac dysfunction by increasing interleukin 10 - Kesherwani, Varun; Chavali, Vishalakshi; Hackfort, Bryan T.; Tyagi, Suresh C.; Mishra, Paras K. (Frontiers in Physiology, 2015)
Increasing evidence suggests that a sedentary lifestyle and a high fat diet (HFD) leads to cardiomyopathy. Moderate exercise ameliorates cardiac dysfunction, however underlying molecular mechanisms are poorly understood. Increased inflammation due to induction of pro-inflammatory cytokine such as tumor necrosis factor-alpha (TNF-α) and attenuation of anti-inflammatory cytokine such as interleukin10 (IL-10) contributes to cardiac dysfunction in obese and diabetics. We hypothesized that exercise training ameliorates HFD- induced cardiac dysfunction by mitigating obesity and inflammation through upregulation of IL-10 and downregulation of TNF-α. To test this hypothesis, eight week old, female C57BL/6J mice were fed with HFD and exercised (swimming 1hr/day for 5 days/week for eight weeks). The four treatment groups: normal diet (ND), HFD, HFD + exercise (HFD + Ex) and ND + Ex were analyzed for mean body weight, blood glucose level, TNF-α, IL-10, cardiac fibrosis by Masson Trichrome, and cardiac dysfunction by echocardiography. Mean body weights were increased in HFD but comparatively less in HFD + Ex. The level of TNF-α was elevated and IL-10 was downregulated in HFD but ameliorated in HFD + Ex. Cardiac fibrosis increased in HFD and was attenuated by exercise in the HFD + Ex group. The percentage ejection fraction and fractional shortening were decreased in HFD but comparatively increased in HFD + Ex. There was no difference between ND and ND + Ex for the above parameters except an increase in IL-10 level following exercise. Based on these results, we conclude that exercise mitigates HFD- induced cardiomyopathy by decreasing obesity, inducing IL-10, and reducing TNF-α in mice.